Reverberation mapping of Active Galactic Nuclei - Hlabathe, Michael (Department of Astronomy, 2023)
Recent times have seen an increase in observational campaigns aimed at contributing to the overall sample of active galactic nuclei (AGNs) with central super-massive black hole (SMBH) mass estimates using reverberation mapping (RM) technique. RM makes use of the time variability of the broad emission lines from the nearby broad-line region (BLR) to measure their time response or delay (τ) relative to the incident ionizing continuum from the accretion disc. This delay is a consequence of light-travel time effects and directly enables the size of the BLR to be determined as RBLR = cτ (c is speed of light). Assuming virialized motions of the gas clouds in the BLR, and combining the velocity width (∆V ) of a Doppler broadened emission line with RBLR leads to the estimation of the black hole mass M. RM can also be used to measure the accretion-disc size in which the X-ray variability source is assumed to drive UV/optical variations in the accretion disc leading to wavelength-dependent delays that scale as τ ∝ λ 4/3 . Here, both aspects of RM are explored using photometric and spectroscopic observations of 3C 120, PG 2304+043 and SDSS J132447.65+032432.6, with observations emanating from the Southern African Large Telescope (SALT) and Las Cumbres Observatory (LCO) robotic telescopes. The broad emission-line and inter-band continuum delays in these AGNs are measured using the Interpolated Cross-Correlation Function (ICCF) and Continuum REverberation AGN Markov Chain Monte Carlo (CREAM).